Differences of Sleep Disorders Between Vestibular Migraine and Benign Paroxysmal Positional Vertigo - Xue, Hui; Wang, Baojun; Meng, Tianyu; Zhao, Shijun; Wang, Qingyin; Zhang, Xin; Kang, Min; Xiang, Wenping (Frontiers in Psychiatry, 2021)
Introduction: Sleep disorder can affect the overall health and quality of life of patients. This study was conducted to compare the differences of sleep disorders in vestibular migraine (VM) patients and benign paroxysmal positional vertigo (BPPV) patients. Methodology: VM patients, BPPV patients and healthy controls (HCs) were recruited. Pittsburgh sleep quality index (PSQI) and polysomnography monitoring were used as subjective and objective, respectively, evaluation method to evaluate the sleep quality of participants in the latest month. Results: 57 BPPV patients, 48 VM patients and 42 HCs were included in this study. There were 79.16% VM patients, 54.39% BPPV patients and 14.28% HCs with sleep disorders. The difference on the incidence rate of sleep disorders was significant between VM patients and BPPV patients (p=0.008), and significantly higher in both VM group (p<0.00001) and BPPV group (p=0.00004) than in the HCs groups (14.28%). Compared to BPPV patients, the VM patients had the significantly lower sleep efficiency (p<0.001) and N3 (p<0.001), and the significantly higher time of wake-up after sleep onset (p<0.001), N1 (p<0.001) and N2 (p<0.001). Meanwhile, the VM patients had the significantly higher incidence rates of severe obstructive sleep apnea hypoventilation syndrome (p=0.001) and Periodic Leg Movement in sleep (p=0.016). Conclusions: The incidence rate of sleep disorders was significantly higher in both VM and BPPV patients than in the HCs groups. To improve the curative effects, the clinicians should pay more attention to the comorbidity of sleep disorders in treating VM and BPPV.